Hippocampal blood–brain barrier permeability is related to the APOE4 mutation status of elderly individuals without dementia. Issue 6 (June 2021) - Moon, Won-Jin; Lim, Changmok; Ha, Il Heon; Kim, Yeahoon; Moon, Yeonsil; Kim, Hee-Jin; Han, Seol-Heui
Blood–brain barrier (BBB) disruption, modulated by APOE4 mutation, is implicated in the pathogenesis of cognitive decline. We determined whether BBB permeability differed according to cognitive functioning and APOE4 status in elderly subjects without dementia. In this prospective study, 33 subjects with mild cognitive impairment (MCI) and 33 age-matched controls (normal cognition [NC]) underwent 3 T brain magnetic resonance imaging. The Patlak model was used to calculate tissue permeability (Ktrans ). A region-of interest analysis of Ktrans was performed to compare relevant brain regions. Effects of Ktrans on cognitive functioning were evaluated with linear regression analysis adjusted for confounding factors. NC and MCI groups did not differ in terms of vascular risk factors or hippocampal Ktrans, except for hippocampal volume. Hippocampal Ktrans was significantly higher in APOE4 carriers than in non-carriers ( p  = 0.007). Factors which predicted cognitive functioning included hippocampal volume (beta=−0.445, standard error [SE]=0.137, p  = 0.003) and hippocampal BBB permeability (beta = 0.142, SE = 0.050, p  = 0.008) after correcting for age, education, and APOE4 status. This suggests that hippocampal BBB permeability is associated with APOE4 mutation, and may predict cognitive functioning. BBB permeability imaging represents a distinct imaging biomarker for APOE4 mutations in NC and MCI subjects and for determining the degree of APOE4-related pathology.